Deaths of despair: cause-specific mortality and socioeconomic inequalities in cause-specific mortality among young men in Scotland - Allik, Mirjam (Int J Equity Health, 2020)
BACKGROUND: Increasing mortality among men from drugs, alcohol and suicides is a growing public health concern in many countries. Collectively known as “deaths of despair”, they are seen to stem from unprecedented economic pressures and a breakdown in social support structures. METHODS: We use high-quality population wide Scottish data to calculate directly age-standardized mortality rates for men aged 15–44 between 1980 and 2018 for 15 leading causes of mortality. Absolute and relative inequalities in mortality by cause are calculated using small-area deprivation and the slope and relative indices of inequality (SII and RII(L)) for the years 2001–2018. RESULTS: Since 1980 there have been only small reductions in mortality among men aged 15–44 in Scotland. In that period drug-related deaths have increased from 1.2 (95% CI 0.7–1.4) to 44.9 (95% CI 42.5–47.4) deaths per 100,000 and are now the leading cause of mortality. Between 2001 and 2018 there have been small reductions in absolute but not in relative inequalities in all-cause mortality. However, absolute inequalities in mortality from drugs have doubled from SII = 66.6 (95% CI 61.5–70.9) in 2001–2003 to SII = 120.0 (95% CI 113.3–126.8) in 2016–2018. Drugs are the main contributor to inequalities in mortality, and together with alcohol harm and suicides make up 65% of absolute inequalities in mortality. CONCLUSIONS: Contrary to the substantial reductions in mortality across all ages in the past decades, deaths among young men are increasing from preventable causes. Attempts to reduce external causes of mortality have focused on a single cause of death and not been effective in reducing mortality or inequalities in mortality from external causes in the long-run. To reduce deaths of despair, action should be taken to address social determinants of health and reduce socioeconomic inequalities. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12939-020-01329-7.